Urban deprivation in Argentina: A POSET analysis. Issue 6 (3rd August 2020) - Ivaldi, Enrico; Ciacci, Andrea; Soliani, Riccardo
Abstract: The Argentinian case offers many examples of fragmented urban reality, whose deprivation might be fruitfully analysed by deprivation indicators, according to a current trend in literature. Non‐aggregative quantitative method based on the POSET theory offers an alternative approach that may steer clear of the shortcomings of the aggregative approaches. Through our analysis we intend to propose a picture of the Argentinian material and social deprivation. Since our approach does not establish any indicator and avoids absolute hierarchy among areas, it makes a rigorous tool available to public authorities. This allows them the rational choice about where and how intervene, to focus the political action at its best. Our analysis shows that social deprivation is characterized by high variability, which makes it less comparable than material deprivation. Moreover, 72% of the statistical units considered are socially deprived. Resumen: Argentina ofrece muchos ejemplos de una realidad urbana fragmentada, cuya precariedad podría ser analizada de manera beneficiosa mediante indicadores de precariedad, según una tendencia actual de la literatura. El método cuantitativo no agregativo basado en la teoría POSET ofrece un enfoque alternativo que puede evitar las deficiencias de los enfoques agregativos. A través de este análisis, el estudio pretende proponer una imagen de la precariedad material y social de Argentina. Dado que nuestro enfoque no establece ningún indicador y evita la jerarquía absoluta entre áreas, pone a disposición de las autoridades públicas una herramienta rigurosa. Esta, les permitirá tomar una decisión racional sobre dónde y cómo intervenir, para dirigir la acción política de la mejor forma posible. El análisis muestra que la precariedad social se caracteriza por una alta variabilidad, lo que la hace menos comparable a la precariedad material. Además, el 72% de las unidades estadísticas consideradas son socialmente precarias. 抄録: アルゼンチンの事例から分断された都市の現実の多くの例が示され、現在の研究論文の傾向によると、アルゼンチンの貧困は貧困指標によって効果的に分析される可能性がある。POSET理論に基づく非集計定量法が、集計アプローチの欠点を補う代替的アプローチとなる。我々は分析を通して、アルゼンチンの物質的及び社会的貧困の実態を提示する。我々のアプローチは指標を確立せず、地域間の絶対的な階層を回避するため、当局が利用できる厳格なツールとなる。これによって、当局が、最適な政治的措置を行うために、どこでどのように介入するかを合理的に選択することが可能になる。結果から、社会的貧困は大きなばらつきを特徴とていることが明らかとなり、そのため物質的貧困との比較はできない。さらに、調査対象となった統計単位の72%が社会的に貧困である。